Methodical approach to the identification of «points of growth» in industry - Shestakova, Kristina V. (Journal of the Belarusian State University. Economics, 2018)
The article provides approaches to grouping industrial sectors in the terms of determination content and priorities of industrial policy. А methodical approach to identifying «points of growth» in industry is established on the basis of a multilevel grouping of indicators that characterize the qualitative and quantitative aspects of industrial sectors development. The methodological approach allows to group industrial sectors, which makes it possible to identify the priority directions of industrial development and recognize sectors that can be «points of growth» in the future. On the basis ofindustrial sectors grouping have been developed proposals on the content and instruments of industrial policy for each group of industries.
Keywords: industry; industrial policy; «points of growth»; industry development; economic growth; innovation